A PERSPECTIVE OF APPLIED LINGUISTICS AND CODE-SWITCHING ANALYSIS ON BALINESE SPOKEN TEXT - Laba, I Nengah; Hendrawan, I Putu; Putri, Putu Diah Kumala (Denpasar Institute, 2023)
The study of applied linguistics aims to understand and address real-world problems, including language used in social contexts. Language use is an important point of view in applied linguistics. Language code switching can impact how a communication is understood and perceived. The method used in this study is qualitative research method and to gather data observational methods areapplied. This study investigates how social identity construction and communication strategies are affected by code-switching. The ultimate goal of this research is to advance the field of applied linguistics by providing a more sophisticated understanding of spoken text code-switching and its consequences for successful intercultural and multilingual communication. YouTube videos from AryKakul Bali were selected for use as research subjects in this study. The results of the study shows that a practical impact of applied linguistics and code-switching analysis on spoken language take into account the changing nature of language used in social contexts. This data analysis revealed three distinct types of code switching: inter-sentential code switching, intra-sentential code switching, and tag switching. The most common type that appeared from the data used was intra-sentential code switching out of these three types.